Is Carbon Taxes Will Able To Tackle Forest Fires In Indonesia: A Swot Analysis In Search Of Optimal Policy - Firman Tatariyanto (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2023)
The research was inspired by the necessity to implement a comprehensive environmental strategy as a result of more than a decade of forest and land fires in Indonesia that caused haze pollution. Without thorough enforcement and the inability to identify the underlying cause of policy execution, the societal cost resulting from the economic agent's behavior will surpass the individual value and degrade the environment. After briefly describing the current command and control instrument and other arrangements in tackling land and forest fire, we do a SWOT analysis on carbon tax with the theme of preventing pollution damage. Our study shows that the ability of carbon tax policy to identify, increase fire costs, monitor compliance model, and implement a mixed policy will induce a behavioral change in economic agents. Closing the environmental policy gap, this study would be a push factor in drawing policy measures to implement the carbon tax roadmap as one of the last fortress policies in carbon pricing to tackle land and forest fire. Moreover, improving policy design is based on a ‘forward-looking’ approach, not pollution amounts.